The application of discussion method for improving the students' logical thinking skills - Sri Budiyono; Dwi Harta; Agus Yuliantoro (English, 2021)
This study aims to: 1) describe the conditions of Indonesian language learning for class XI students at Vocational High School 1 of BYL; 2) describe and explain the events of Cycle I and Cycle 2 in Indonesian language learning when using on-the-spot learning using the discussion method; 3) describe and explain the effectiveness of Indonesian language learning with conventional methods and deep discussion methods. This study used a classroom action research design with four steps, namely, 1) planning: 2) implementation; 3) observation; 4) reflection. In the initial step (planning) the researcher pays attention to things that are strategic towards the implementation steps that are carried out, then the researcher takes action to do things that need to be done in the next process, namely by collaborating with colleagues who are partners to discuss and help with implementation of action research is carried out, as well as trying to condition the learning in the classroom carried out in the research. The results of this study indicate that: (1) students need to work and learn together to decide something that is difficult when faced; (2) learning in a happy condition creates a safe, comfortable, calm, and controlled atmosphere; (3) The results of the effectiveness test show that learning using the discussion method results in better achievement than learning using conventional methods.